Gremlin-2 is a novel tumor suppressor that negatively regulates ID1 in breast cancer - Jiwoo Jung; Na Hui Kim; Jayeon Park; Dayeon Lim; Minji Kwon; World Gil; Suyeon Jung; Minjeong Go; Chaeeon Kim; Ye Hwang Cheong; Mee-Hyun Lee; Hee Sun Park; et al. (Breast Cancer Research, 2024)
Abstract Background Breast cancer is one of the most common cancers in women and is closely associated with obesity. Gremlin-2 (GREM2), an antagonist for bone morphogenetic proteins (BMPs), has been considered an inhibitor of adipogenic differentiation in adipose-derived stromal/stem cells. However, the role of GREM2 in breast cancer cells remains largely unknown, and its signaling mechanism has yet to be clarified. Methods Bioinformatics analysis was conducted using public databases. Breast cancer cells overexpressing mock or GREM2 were used for in vitro and in vivo studies. Cell viability, colony formation, migration, and animal studies were performed to investigate the role of GREM2 in breast cancer cells. Screening of target genes affected by GREM2 overexpression in breast cancer cells was performed through RNA sequencing (RNA-seq) analysis. Results The expression level of GREM2 mRNA was significantly reduced in both breast cancer tissues and cell lines. Kaplan-Meier analysis showed that low expression of GREM2 and high methylation of the GREM2 promoter were each associated with poor patient survival. The low mRNA expression of GREM2 in breast cancer cells was increased by the demethylating agent decitabine. Breast cancer cells overexpressing GREM2 decreased cell proliferation when compared to control cells, both in vitro and in vivo. Through comparison of RNA-seq analysis between cell lines and tissue samples, gene ontologies that were consistently upregulated or downregulated by GREM2 in breast cancer were identified. In particular, the expression of inhibitor of DNA-binding-1 (ID1) was repressed by GREM2. BMP2 is one of the upstream regulators that increases the expression of ID1, and the expression of ID1 reduced by GREM2 was restored by overexpression of BMP2. Also, the migration ability of breast cancer cells, which had been suppressed by GREM2, was restored by BMP2 or ID1. Conclusions Low expression of GREM2 in breast cancer cells is associated with hypermethylation of the GREM2 promoter, which may ultimately contribute to poor patient survival. GREM2 participates in regulating the expression of various genes, including ID1, and is involved in suppressing the proliferation of breast cancer cells. This suggests that GREM2 has the potential to act as a novel tumor suppressor in breast cancer.